Carbon nanotube-polyoxometalate nanohybrids as efficient electro-catalysts for the hydrogen evolution reaction. (March 2022) - Jawale, Dhanaji V.; Fossard, Frédéric; Miserque, Frédéric; Geertsen, Valérie; Teillout, Anne-Lucie; de Oliveira, Pedro; Mbomekallé, Israël M.; Gravel, Edmond; Doris, Eric
Abstract: Electroactive hybrid nanomaterials were assembled by non-covalent, layer-by-layer deposition of tungsten-based polyoxometalates on carbon nanotubes. Chemical functionalization permitted access to nanotubes densely and homogeneously covered with polyoxometalates. Electrochemical characterisation of the nanohybrids highlighted the beneficial contribution of the nanotube platform to the overall stability of the immobilized POM species, and to the enhancement of their catalytic performances when applied to the hydrogen evolution reaction. Graphical abstract: Image 1